DETERMINING THE STRENGTH OF HAND GRIP FOR HEALTHY ADULTS IN RELATION WITH HAND LENGTH, FOREARM CIRCUMFERENCE, BMI AND HAND DOMINANCE (International Journal of Physiotherapy, 2016)
Background: Hand-grip strength studies with healthy adults have shown correlation between anthropometric variables and hand grip strength. There is dearth in literature in population of Saudi Arabia. The objective of this study is to describe normative data to evaluate the relationship between handgrip strength and other anthropometric variables especially hand length, forearm circumference with regard to dominant hand, among healthy males in Abha, Saudi Arabia, using a Hand held dynamometer.Methods: A sample of 99 male adults from the population of Abha, Saudi Arabia, ages 20 to 72 years were tested using standardized positioning and instructions. A Hand–held dynamometer was used to measure grip strength in kilograms.Results: Low to medium correlation (significant) is found between all the variables and HGS. Age is negatively correlated. A stepwise regression predicts that hand length, age, forearm girth circumference are the three significant variables of hand grip strength. An ANOVA proves that hand grip strength is less for subjects above 60 years; hand grip strength is higher for subjects with extra-large forearm girth circumference.Conclusion: Normative values hand grip strength in population of Saudi Arabia is established through this study. The hand grip strength is influenced by hand length, hand girth circumference as well as age category of the subjects and these variables can be better predictors while clinically rehabilitating hand patients.